OBOWIĄZEK UDZIELENIA POMOCY W PRZYPADKU SPRZECIWU OSOBY ZAGROŻONEJ W ŚWIETLE ART. 162 KODEKSU KARNEGO - Julia Kosonoga-Zygmunt (Zeszyty Prawnicze)
The Duty of Medical Personnel to Provide Medical Assistance to a Person In Grave Danger in the Event of His/Her Refusal to Accept Help, in the Light of Art. 162 of the Polish Criminal Code